Environment and development : (IVM, 1987)
Symposium at the occasion of the publication of "Our common future", report of the Brundtland Commission, World Commission on Environment and Development and at the occasion of the 15th anniversary of the Institute for Environmental studies at the Free University in Amsterdam.